Venetoclax and Daratumumab combination treatment demonstrates pre-clinical efficacy in mouse models of Acute Myeloid Leukemia - Jayna J Mistry; Charlotte Hellmich; Amelia Lambert; Jamie A Moore; Aisha Jibril; Angela Collins; Kristian M Bowles; Stuart A Rushworth (Biomarker Research, 2021)
Abstract Acute myeloid leukemia (AML) remains an incurable malignancy despite recent advances in treatment. Recently a number of new therapies have emerged for the treatment of AML which target BCL-2 or the membrane receptor CD38. Here, we show that treatment with Venetoclax and Daratumumab combination resulted in a slower tumor progression and a reduced leukemia growth both in vitro and in vivo. These data provide evidence for clinical evaluation of Venetoclax and Daratumumab combination in the treatment of AML.